The development of the scale towards effectiveness of school principals in communication process - Özmen, Fatma; Yörük, Sinan (My University, 2007)
In this study, to determine the effectiveness of the school principals in the process of communication, related to the professional development of teachers, a scale was aimed to be developed on the basis of educators' views. For this, initially 38 five point rating scale Likert type items conveying negative and positive connotations were developed using the review of literature and implications held through the interviews realized with the educators in the primary and secondary schools. Later, according to the thoughts of professionals, some of the items were removed and as a result 26 items were obtained. There are five educational districts in the city of Elazig, and a primary school was chosen randomly from each district and the instrument was conducted to the educators working at these schools. As total, 132 participants replied the scale. The scale has one factor and it measures the effectiveness of schools principals during communication process, for the profesisonal growth of teachers.
Okul yöneti?ci?leri?ni?n, i?leti?si?m süre?indek?i etkilili?i ölç?inin geliştirilmesi
Keywords: Communication; Instrument; Reliability; School principals; Validity